Bioaccumulation of Trace Elements from Aqueous Solutions by Selected Terrestrial Moss Species - Świsłowski, Paweł; Nowak, Arkadiusz; Wacławek, Stanisław; Silvestri, Daniele; Rajfur, Małgorzata (Biology, 2022)
The interrelationship between metal concentrations in mosses and their surroundings prompts research toward examining their accumulation properties, as it is particularly important for their usage in biomonitoring studies that use mosses. In this study, the kinetics of elemental sorption in three moss species (Pleurozium schreberi, Dicranum polysetum, and Sphagnum fallax) were investigated under laboratory conditions. Sorption from metal salt solutions was carried out under static conditions with decreasing elemental concentration. Functional groups responsible for binding metal cations to the internal structures of the mosses were also identified. It was shown that the equilibrium state was reached after about 60 min. Under the conditions of the experiment, in the first 10 min of the process, about 70.4-95.3% of metal ions were sorbed from the solution into the moss gametophytes by P. schreberi (57.1-89.0% by D. polysetum and 54.1-84.5% by S. fallax) with respect to the concentration of this analyte accumulated in the mosses at equilibrium. It can be assumed that the exposure of mosses with little contamination by heavy metals in an urbanized area under active biomonitoring will cause an increase in the concentration of these analytes in proportion to their concentration in atmospheric aerosols. In the case of P. schreberi and D. polysetum, the O-H/N-H band was enormously affected by the adsorption process. On the other hand, FTIR (Fourier transform infrared spectroscopy) analysis of S. fallax after adsorption showed slight changes for most of the bands analyzed. Based on this study, it can be concluded that mosses can be used as, for example, a biomonitor in monitoring of urban ecosystems, but also in the phytoremediation of surface waters.
Keywords: mosses; bioaccumulation; FTIR; heavy metals; urban areas; sorption